The Effect of a Training Intervention Program on Fall- Related Motor Performance in the Male Elderly without Regular Physical Activity - Daryoush Khajavi; Ahmad Farrokhi; Ali Akbar Jaberi Moghadam; Anushiravan Kazemnejad (University of Tehran, 2013)
The aim of this research was to examine the effect of a training interventionprogram on fall-related motor performance in the male elderly with no regularphysical activities. For this purpose, 39 out of 130 participants in screen test wereselected and assigned to training group (n=20) and control group (n=19). Subjectsaged between 60 and 70 in experimental were 73.68% and in the control group43.75% and subjects aged 71 and above were 26.31% in the experimental groupand 56.25% in the control group. Experimental group participated in a 10-weekintervention program (3 sessions per week and 90 minutes per session). Data werecollected with 30-s seat, sit and reach, one-leg standing (eyes open and closed), upand go, 10-meter walk and 10-meter obstacle walk tests. In this semi-experimentalresearch, Kolmogorov-Smirnov and independent t test was used to analyse motorperformance measures. Results indicated a significant improve in mean scores oflower extremity strength (27.37 rep), flexibility (29.28 cm), static balance with eyesopen (60.94 sec) and closed (19.36 sec), agility and dynamic balance (4.10 sec),10-meter walk (3.35 sec) and 10-meter obstacle walk (4.03 sec) in the experimentalgroup after the 10-week training intervention program (P<0.05). The findingsconfirmed the effect of training interventions (especially strength training) onimproving fall-related motor performance and preventing probable falls in theelderly.